Numerical analysis of the influence of sample stiffness and plate shape in the Brazilian test (2015)
Due to the heterogeneity of rocks, their tensile strength is around 10% of their compressive strength, which means that breakage is mainly caused by tensile stress. The measure of tensile stress is very difficult due to rock fragility, so it has usually been measured by indirect measurement methods , including the Brazilian test. However, recent works indicate that the tensile strength values obtained through the Brazilian test must be increased by almost 26%. To understand this divergence, indirect tensile tests have been monitored. The aim is to know the material deformation and load increase by means of stepwise regression. Stress fields in slightly deformed samples are analyzed and modeled (3D finite differences) with loads applied on flat and curved plates and different Young's modulus. Finally, the results are analyzed and compared with strength values reported using Timoshenko theory and Hondros' approximation.